2002
DOI: 10.1111/j.1365-2621.2002.tb10643.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Gelation of β‐lactoglobulin in the Presence of Iron

Abstract: To protect and transport iron, we investigated the trapping properties of a network formed from ␤ ␤ ␤ ␤ ␤-lactoglobulin. We studied the influence of different parameters-pH, iron, and protein concentrations-on gel properties (optical and mechanical properties, WHC, and microstructure). For all conditions tested, the results show the formation of a cold gel in the presence of iron. The mechanical properties reveal that the elastic behavior and the strength of rupture increase with higher protein concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
54
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 41 publications
10
54
0
2
Order By: Relevance
“…10,[12][13][14] In a previous study, we investigated the cold gelation of ␤-lg induced by the addition of Fe 2ϩ , in order to protect iron from environmental conditions. 15 Our results show that the macroscopic properties obtained for Fe 2ϩ -induced ␤-lg cold gels exhibit similarities with those obtained in studies with different cation (Ca 2ϩ , Mg 2ϩ , Na ϩ )-induced cold gels, suggesting that the cation-protein interactions would be of similar nature, where the electrostatic interaction would play a predominant role. 10,11,15,16 Moreover, we demonstrated that different types of gels could be obtained depending on pH conditions and protein and/or iron concentration.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…10,[12][13][14] In a previous study, we investigated the cold gelation of ␤-lg induced by the addition of Fe 2ϩ , in order to protect iron from environmental conditions. 15 Our results show that the macroscopic properties obtained for Fe 2ϩ -induced ␤-lg cold gels exhibit similarities with those obtained in studies with different cation (Ca 2ϩ , Mg 2ϩ , Na ϩ )-induced cold gels, suggesting that the cation-protein interactions would be of similar nature, where the electrostatic interaction would play a predominant role. 10,11,15,16 Moreover, we demonstrated that different types of gels could be obtained depending on pH conditions and protein and/or iron concentration.…”
Section: Introductionsupporting
confidence: 77%
“…15 Our results show that the macroscopic properties obtained for Fe 2ϩ -induced ␤-lg cold gels exhibit similarities with those obtained in studies with different cation (Ca 2ϩ , Mg 2ϩ , Na ϩ )-induced cold gels, suggesting that the cation-protein interactions would be of similar nature, where the electrostatic interaction would play a predominant role. 10,11,15,16 Moreover, we demonstrated that different types of gels could be obtained depending on pH conditions and protein and/or iron concentration. When iron/protein ratios were low and the pH value close to 7, gels were homogeneous and characterized by an elastic behavior and a high resistance to rupture, suggesting that strong particle-particle interactions occurred.…”
Section: Introductionsupporting
confidence: 77%
“…These include the chemical environment of aqueous solution (pH, protein concentration and ionic strength), and/or addition of electrically charged species (cold gelation) (Debeaufort et al, 1998;. Development and production of whey protein nanosystems can be tailored by small changes in these external factors (Mulvihill and Kinsella, 1988;Lef' evre and Subirade, 2000;Remondetto et al, 2002). Temperature.…”
Section: Influence Of Environmental Factors On Protein Gelationmentioning
confidence: 99%
“…Concentration plays an important effect in protein aggregation, particularly when denaturation is induced by heat; in this case, the tendency of a protein to aggregate is higher when its concentration is high (Wehbi et al, 2005). Equally, when a salt is added to a heat-denatured protein solution, the concentration of protein has a major influence on the rheological properties of the solutions; at low protein concentrations the heat-denatured protein will tend to form a viscous solution-yet above the critical protein concentration, a gel is obtained (cold gelation) (Remondetto et al, 2002;Ramos et al, 2012b The salt type to adjust ionic strength is other condition that should be considered. For instance, calcium and magnesium (divalent ions) can induce aggregation via electrostatic shielding, ion/hydrophobic interactions and cross linking with negatively charged carboxylic groups of neighboring whey protein molecules-leading to the establishment of protein-cat-ion-protein bridges.…”
Section: Protein Concentrationmentioning
confidence: 99%
“…Sodium or calcium ion induced or "cold-set" gels obtained from whey protein were extensively investigated (BArBut & Foegeding, 1993;BryAnt & MCCLementS, 1998;Foegeding, 2007). There is very little research done on "cold-set" gels Acta Alimentaria 43,2014 obtained by using other cations like magnesium or iron (Remondetto et al, 2002;Remondetto & SuBirAde, 2003;DA SiLvA & DeLgAdo, 2009). No results were presented on aerated gels obtained by the addition of the above ions.…”
mentioning
confidence: 99%